Determinantes sociais e pedagógicos da evasão escolar: um estudo no Instituto Federal Baiano – campus Serrinha - Santos, Julliana Pena de Carvalho (2022)
School dropout is a complex phenomenon that causes educational, economic, familiar, and social consequences. In addition, dropout is notable for its many different causes, which can manifest themselves alone or through a combination of factors, such as the need to work, time dedicated to studies, difficulties with transportation, illness, and pregnancy. This work aimed to understand the social and pedagogical determinants that corroborate the dropout at the Federal Institute of Bahia, Serrinha campus, of students enrolled in technical courses – integrated to high school and subsequent – from 2016 to 2019. The qualitative approach was used for the case study type and descriptive research. The data analysis shows that the factors contributing to school dropout are diverse, complex, and heterogeneous, having a significant connection between the student and the context in which he lives. Identified that dropout students have a profile aged between 21 and 40 years, being mostly female and with a family income, that does not exceed two minimum wages. It also showed that although the student assistance actions were not able to avoid the dropouts, due to the existence of external factors, they were extremely important for the permanence and success of several students, thus avoiding a greater number of dropouts.